Implementasi Nilai Pendidikan Karakter Islam Dalam Pembelajaran Sains - Nurhilaliyah (Jurnal Ilmu Pendidikan Guru Sekolah Dasar dan Usia Dini, 2025)
Science learning plays a crucial role in the process of shaping human character, particularly through the skills and habits of scientific thinking that can serve as a foundation for moral, character, and ethical development in national education. Science learning functions as a benchmark or reference point for character formation, helping individuals develop strong personal integrity. This study aims to understand the concept of character education from the perspective of Hadith through contextual and non-contextual analysis. Data were collected from various references and analyzed using an interpretive approach focused on extracting core meanings. The findings of this research indicate that the Hadiths examined in this study contain patterns and guidelines for human behavior. Character education becomes more explicit through the teachings of the Prophet Muhammad, especially those Hadiths that emphasize moral and character formation. The abundance of Hadiths related to character requires Muslim scholars to fully utilize character education based on the Qur’an and Hadith. The Qur’an and the Prophet’s Hadith can be applied as foundational principles and within various domains of education, especially in response to the increasing cases of moral and criminal issues occurring within Indonesia’s educational environment. As students, we must be able to address and neutralize these issues through a Sharia-based perspective that refers to the Prophet’s Hadiths and the Qur’an.